APPLICATION OF SHARIA ACCOUNTING IN MURABAHAH AND MUDHARABAH FINANCING AT BMT FAUZAN AZHIIMA PAREPARE - Ahmad Majid, Annisa Nurul Fadilah (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2024)
Sharia accounting is an emerging area within accounting studies that is founded on truth values based on Islamic law. It is governed by PSAK, which is developed and published by the Financial Accounting Standards Council. The numerous opinions regarding sharia financial institutions not yet fully implementing sharia accounting in accordance with PSAK motivated the author to delve deeper into the application of accounting at BMT Fauzan Azhiima Parepare, particularly in the areas of murabahah and mudharabah financing. This research adopts a qualitative approach, utilizing field research methods, and primary data collection through observation and interviews. The study was conducted at BMT Fauzan Azhiima Parepare, involving in-depth interviews with seven informants. The findings of this research indicate that (1) the implementation of sharia accounting at BMT Fauzan Azhiima Parepare is reflected in its financial statements and the execution of its murabahah and mudharabah programs, which are in line with the recognition, measurement, presentation, and disclosure of transactions as prescribed by PSAK. (2) Sharia accounting appears to positively impact BMT Fauzan Azhiima Parepare by facilitating its ability to assess sharia financial positions regarding existing programs or transactions. Margins and profit-sharing are negotiated based on agreements between both parties, ensuring that each transaction aligns with the capabilities and needs of BMT Fauzan Azhiima Parepare’s customers.